The Role Of Legislative Drafting Legislation Of The Regional Office Of The Ministry Of Law and Human Rights In The Formation Of Regional Regulations - Manurung, Rosa Desi Natalisma; Simamora, Janpatar (Indonesian Journal of Law and Justice, 2025)
To reduce differences between laws and regulations, the Regional Office of the Ministry of Law and Human Rights must be involved in the creation of regional regulations, both in terms of content and harmonization efforts. The extent to which the role of the Regional Office in the context of harmonization and factors is a research issue. Obstacles and how to build a consistent pattern of cooperation with the regional government sector. The research findings show that the Regional Office has actually participated in harmonization. However, there has been no significant participation in the creation of regional legislative initiatives. This is due to several things, including the problem of sectoral egos of the regional government, lack of infrastructure, and lack of support from the regional office. To ensure that the existence of legislative designers is recognized and considered, the regional office must be able to persuade the regional government directly. Based on the research findings, it can be concluded that the regional office plays an important role in carrying out the function of facilitating the creation of regional legal products, starting with the stages of plaining, preparation, and announcement of regional regulations.